AID/APOBEC-like cytidine deaminases are ancient innate immune mediators in invertebrates - Mei-Chen Liu (Nature Portfolio, 2018)
The AID/APOBEC cytidine deaminase family are nucleic acid editors, important for antigen receptor expression and thought to have evolved along with vertebrate adaptive immunity. Here the authors show this family may have evolved prior to adaptive immunity as members with cytidine deaminase activity are present and functional in invertebrate sea urchins and brachiopods.